Science technology innovation roadmap for sustainable development goals- international experiences and recommendations for Vietnam - Giang, Dang Thu; Anh, Nguyen Hong; Hai, Ta Doan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
In September 2015, the United Nations (UN) approved the Global Agenda 2030 (Agenda 2030), which defines science, technology and innovation is a tool to achieve sustainable development goals. International experience shows that in order to successfully implement targeted sustainable development, one of the important solutions is to tranfer sustainable development goals into key tools and link strategies, plans, science technology and innovation roadmap with sustainable development goals. Experiences of some countries in the development of science, technology and innovation roadmap for sustainable development goals bring good implications for Vietnam in developing solutions to utilize science, technology and innovation for sustainable development goals of Vietnam. Code: 20122103